Download presentation
Presentation is loading. Please wait.
Published byWalter Hunt Modified over 9 years ago
1
9.1 – Multiplying & Dividing Rational Expressions
2
Ex. 1 Simplify. a. 30bc 12b 2
3
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 12b 2
4
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c 12b 2
5
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c 12b 2 6·2·b·b
6
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c 12b 2 6·2·b·b
7
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c 12b 2 6·2·b·b
8
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c 12b 2 6·2·b·b
9
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b
10
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5
11
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = x 2 – 4x – 5
12
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = x 2 – 4x – 5
13
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5
14
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5
15
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5 (x – 5)(x + 1)
16
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5 (x – 5)(x + 1)
17
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5 (x – 5)(x + 1)
18
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5 (x – 5)(x + 1)
19
9.1 – Multiplying & Dividing Rational Expressions Ex. 1 Simplify. a. 30bc 12b 2 30bc = 6·5·b·c = 5c 12b 2 6·2·b·b 2b b. 2x 2 – 10x x 2 – 4x – 5 2x 2 – 10x = 2x(x – 5) x 2 – 4x – 5 (x – 5)(x + 1) = 2x x + 1
20
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3
21
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 5b 16a 3
22
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3
23
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3
24
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3 = 2·2·3·5·a·b·b
25
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3 = 2·2·3·5·a·b·b 2·2·2·2·5·a·a·a·b
26
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3 = 2·2·3·5·a·b·b 2·2·2·2·5·a·a·a·b
27
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3 = 2·2·3·5·a·b·b 2·2·2·2·5·a·a·a·b
28
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3 = 2·2·3·5·a·b·b 2·2·2·2·5·a·a·a·b = 3·b 2·2·a·a
29
Ex. 2 Simplify each expression. a. 4a. 15b 2 5b 16a 3 4a. 15b 2 = 4a · 15b 2 5b 16a 3 5b · 16a 3 = 2·2·3·5·a·b·b 2·2·2·2·5·a·a·a·b = 3·b = 3b 2·2·a·a 4a 2
30
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2
31
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = x 2 + 4x + 3 x – 2
32
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2) x 2 + 4x + 3 x – 2
33
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)
34
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)
35
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1) (x – 2)
36
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1)
37
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2)
38
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2)
39
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2)
40
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2)
41
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2)
42
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2) = 3(x + 4) (x + 3)
43
b. x 2 + 2x – 8. 3x + 3 x 2 + 4x + 3 x – 2 x 2 + 2x – 8. 3x + 3 = (x + 4)(x – 2). 3(x + 1) x 2 + 4x + 3 x – 2 (x + 3)(x + 1)(x – 2) = 3(x + 4)(x – 2)(x + 1) (x + 3)(x + 1)(x – 2) = 3(x + 4) = 3x + 12 (x + 3) x + 3
44
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3
45
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 15a 3 b 3 5ab 3
46
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y 15a 3 b 3 5ab 3 15a 3 b 3
47
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2
48
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2
49
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2 = 2·2·5·a·b·b·b·x·x·y
50
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2 = 2·2·5·a·b·b·b·x·x·y 2·3·5·a·a·a·b·b·b·x·y·y
51
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2 = 2·2·5·a·b·b·b·x·x·y 2·3·5·a·a·a·b·b·b·x·y·y
52
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2 = 2·2·5·a·b·b·b·x·x·y 2·3·5·a·a·a·b·b·b·x·y·y
53
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2 = 2·2·5·a·b·b·b·x·x·y 2·3·5·a·a·a·b·b·b·x·y·y = 2·x 3·a·a·y
54
Ex. 3 Simplify each expression. a. 4x 2 y ÷ 2xy 2 15a 3 b 3 5ab 3 4x 2 y ÷ 2xy 2 = 4x 2 y. 5ab 3 15a 3 b 3 5ab 3 15a 3 b 3 2xy 2 = 2·2·5·a·b·b·b·x·x·y 2·3·5·a·a·a·b·b·b·x·y·y = 2·x = 2x 3·a·a·y 3a 2 y
55
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3
56
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 – 9 x + 3
57
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12 x 2 – 9 x + 3 x 2 – 9
58
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2
59
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3)
60
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3) (x + 3)(x – 3)
61
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2)
62
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3)
63
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2)
64
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2)
65
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2)
66
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2)
67
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2)
68
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2)
69
b. x 2 + x – 12 ÷ x + 2 x 2 – 9 x + 3 x 2 + x – 12 ÷ x + 2 = x 2 + x – 12. x + 3 x 2 – 9 x + 3 x 2 – 9 x + 2 = (x + 4)(x – 3). (x + 3) (x + 3)(x – 3) (x + 2) = (x + 4)(x – 3)(x + 3) (x + 3)(x – 3)(x + 2) = x + 4 x + 2
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.